2016
DOI: 10.1038/nprot.2016.153
|View full text |Cite
|
Sign up to set email alerts
|

Generating high-purity cardiac and endothelial derivatives from patterned mesoderm using human pluripotent stem cells

Abstract: Human pluripotent stem cells (hpscs) provide a valuable model for the study of human development and a means to generate a scalable source of cells for therapeutic applications. This protocol specifies cell fate efficiently into cardiac and endothelial lineages from hPSCs. The protocol takes 2 weeks to complete and requires experience in hPSC culture and differentiation techniques. Building on lessons taken from early development, this monolayer-directed differentiation protocol uses different concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
158
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(168 citation statements)
references
References 49 publications
(82 reference statements)
2
158
0
Order By: Relevance
“…We recently generated a differentiation method involving modulation of activin A and BMP4 stimulation to direct anterior vs posterior-like mesoderm that gives rise to cell populations reflecting cardiogenic fates vs. blood forming lineages, respectively, from hPSCs (Palpant et al, 2017; Palpant et al, 2015b). Using well established cues from developmental biology we can generate cardiogenic mesoderm, an anterior primitive streak lineage that is directed primarily through stimulation of activin A and gives rise to cardiomyocytes with high efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…We recently generated a differentiation method involving modulation of activin A and BMP4 stimulation to direct anterior vs posterior-like mesoderm that gives rise to cell populations reflecting cardiogenic fates vs. blood forming lineages, respectively, from hPSCs (Palpant et al, 2017; Palpant et al, 2015b). Using well established cues from developmental biology we can generate cardiogenic mesoderm, an anterior primitive streak lineage that is directed primarily through stimulation of activin A and gives rise to cardiomyocytes with high efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, the isolation of pluripotent stem cells, first in mouse followed by human 50 (Evans and Kaufman, 1981;Thomson et al, 1998), and the more recent discovery of deriving pluripotent stem cells from somatic cell types (iPSCs) (Takahashi and Yamanaka, 2006), is a means to study lineage-specific mechanisms underlying development and disease to broaden our capacity for biological therapeutics (Palpant et al, 2017). Pluripotent stem cells are capable of unlimited selfrenewal and can give rise to specialized cell types based on stepwise changes in the transcriptional 55 networks that orchestrate complex fate choices from pluripotency into differentiated states.…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that hCD2 + Treg, supernatant of Treg or AREG significantly increased %Ki67 + cTnT + cells among total cTnT + cells (Fig 6B). To recapitulate the same effect on human cardiomyocytes, we differentiated beating cardiomyocytes from human embryonic stem cells as previously described 31 (hESC-CM, Fig 6C). We cocultured relatively mature, less proliferative hESC-CM (day 76) with supernatant of Treg cultures or recombinant human AREG protein for 3 days.…”
Section: Resultsmentioning
confidence: 99%
“…For human cardiomyocytes, cardiomyocytes were derived from hESCs as previously described 31 . Cardiomyocytes were generated with a sequential administration of growth factors (Fig 6C).…”
Section: Methodsmentioning
confidence: 99%